The Influence of Electronic Service Quality and Electronic Recovery on Online Re-Purchase Intention: Role of E-Loyalty as Intervening Variable - Erwin Dhaniswara; Suluh Sri Wahyuningsih; Handry Eldo; Asri Ady Bakri; Agus Junaidi (SEULANGA SYSTEM PUBLISHER, 2023)
This study intends to examine how online service quality and online recovery affect online loyalty and how they affect consumers' willingness to repurchase online. In this study, a non-probability sampling strategy with a purposeful sampling procedure was applied. A sample of 100 respondents who had purchased products from the marketplace were given questionnaires in order to obtain the data. The data in this study are analyzed using the Partial Least Square (PLS) method. The findings of this study demonstrate that online repurchase intention and electronic service quality have an impact on online loyalty. This study also discovered that electronic service quality has an impact on online repurchase intention via electronic loyalty. Through electronic loyalty, electronic recovery also has an impact on online repurchase intention.